Մաշտոցեան Մատենադարանի ձեռագրական հաւաքածուները - Տէր-Վարդանեան, Գէորգ
As of late November 2022, the collection of complete Armenian manuscripts of Matenadaran is 11 363 items. It was formed in eight stages: 1. The “old collection of Etchmiadzin” took shape spontaneously. 2. The purposeful collection of manuscripts during the cultural awakening in the days of Catholicos Gevorg IV of Constantinople (1866–1882) and his successors: the “Gevorgian” collection. 3. The collection of manuscripts from monasteries, churches and individuals in large dioceses under the jurisdiction of the Mother See of Holy Etchmiadzin (Eastern Armenia and elsewhere) during 1893–1915. 4. The saving of collections in Western Armenia, particularly in Vaspurakan and Taron, which was one of the important cultural results of the self-defense of Van (April–May 1915). 5. The enrichment of the collection of the nationalized Matenadaran in 1922– 1940. 6. The period of transmissions from other organizations, the systematization of the manuscript and diplomatic collections, their enrichment by transfers, purchases and donations in 1941–1962. 7. The all-Armenian and diasporal period of comings-in: 1965–1991, continued with variable intensity until the disintegration of the Soviet Union and the gaining of independence by Armenia. 8. The period of independence. Besides complete Armenian manuscripts, Matenadaran also possesses: 1. Fragments of Armenian manuscripts – 2245 items. 2. Armenian amulet scrolls – 561 items. 3. A collection of new Armenian manuscripts (second half of the 19th, early 20th cc.) – 490 items. 4. A collection of unpublished catalogues – 182 items. There are also descriptions of lost manuscripts and collections; the most important among them is the huge work of Mesrop Magistros Ter-Minasyan, the “Comprehensive Catalogue of Armenian Manuscripts,” which describes 23 000 items known to the author in the 1930s. 5. A collection of manuscripts in Arabic script (in the Arabic, Persian and Turkish languages) – 2733 items. 6. Fragments of Arabic-script manuscripts – 612 items.7. Fragments of Arabic-script amulets (in Arabic and Persian) – 54 items. 8. A collection of manuscripts in other languages (all other scripts besides the Armenian and Arabic) – 381 items. 9. A collection of fragments in other languages – 152 items, folios from Syriac, Hebrew, Ethiopian, Latin, Japanese, Greek, Slavonic, Georgian manuscripts and three Egyptian Papyri. The manuscript collections as of late November 2022, are the following: the total number of the five Armenian collections is 14 843, and of the other collections, 3 932, altogether, 18 775 items. The known number of convolutes (two or more manuscripts in one codex) in the main collection of Armenian manuscripts (№№ 1–11 363) is 1818; 18 775+1818 = 20 593 items. The number of guard-leaves in the main collection of Armenian manuscripts (№№ 1–11 363) is 2145; altogether, Matenadaran houses 22 738 manuscript items. Собрание полных армянских рукописей по состоянию на конец ноября 2022 г. насчитывает 11 363 единицы. Оно формировалось в восемь основных этапов. 1. «Старая коллекция Эчмиадзина»: создавалась стихийно. 2. Целенаправленное собирание рукописей в период культурного пробуж- дения при католикосе Георге IV Константинопольском (1866-1882) и его по- следователях: собрание «Георгян». 3. Собирание монастырских, церковных и частных коллекций и отдель- ных рукописей по крупным епархиям, находящимся в юрисдикции Св. Пре- стола в Эчмиадзине (Восточная Армения и др.), 1893-1915 гг. 4. Спасение собраний Западной Армении, особенно Васпуракана и Та- рона, что явилось одним из важных культурных результатов известной само- обороны Вана (апрель-май 1915 г.). 5. Пополнения коллекции национализированного Матенадарана, 1922- 1940 гг. 6. Период передачи из других организаций, систематизации рукописных и дипломатических коллекций и пополнения за счет передач, покупок и даре- ний: 1941-1962 гг. 7. Всеармянский или диаспоральный период поступлений – 1965-1991 гг. Продолжался с переменной интенсивностью до распада Советского Союза и обретения Арменией независимости. 8. Период независимости Армении. В Матенадаране хранятся также: 1. Собрание фрагментов армянских рукописей – 2245 единиц. 2. Собрание армянских свитков-оберегов – 561 единица. 3. Собрание новых армянских рукописей (вторая половина XIX, начало XX века) – 490 единиц. 4. Собрание неопубликованных каталогов, 182 единицы. Имеются и опи- сания несохранившихся рукописей и коллекций. Наиболее значимое из них – гигантский труд архиепископа Месропа Магистроса Тер-Мовсисяна «Общий каталог армянских рукописей», в котором описываются 23 000 единицы, из- вестные автору по состоянию на 1930-е годы. 5. Собрание рукописей арабского письма (на арабском, персидском и ту- рецком) – 2733 единицы. 6. Коллекция арабографических фрагментов – 612 единиц. 7. Коллекция арабографических (на арабском и персидском) оберегов – 54 единицы. 8. Собрание иноязычных рукописей (любого другого письма, кроме ар- мянского или арабского) – 381 единица. 9. Собрание иноязычных фрагментов – 152 единицы (листы из сирийских, еврейских, эфиопских, латинских, японских, греческих, славянских, грузин- ских рукописей, а также три египетских папируса). На конец 2022 года рукописные собрания Матенадарана им. Маштоца вы- глядит следующим образом: общее количество рукописей пяти армянских кол- лекций составляет 14 843, арабоязычных и иноязычных коллекций – 3 932, итого – 18 775 единиц хранения. Известное число конволютов (двух и более разных рукописей, сплетен- ных в один кодекс) в основном собрании армянских рукописей (№№ 1-11 363) – 1818, то есть в целом фонд армянских рукописей содержит 20 593 ед. (18 775+1818). Число фрагментов на защитных листах в основном собрании армянских рукописей (№№ 1-11 363) составляет 2145, то есть всего в Матенадаране нахо- дится 22 738 рукописных единиц хранения.
Keywords: Մատենագիտություն